Management of pregnancy and obstetric complications in prehospital trauma care: faculty of prehospital care consensus guidelines. Issue 5 (6th March 2017) - Battaloglu, E; Porter, K
Abstract : This consensus statement seeks to provide clear guidance for the management of pregnant trauma patients in the prehospital setting. Pregnant patients sustaining trauma injuries have certain clinical management priorities beyond that of the non-pregnant trauma patients and that if overlooked may be detrimental to maternal and fetal outcomes.